Pengembangan Kreativitas Guru dalam Pembelajaran Kreatif Pelajaran Bahasa Inggris - Helda Jolanda Pentury (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2017)
Abstract: Creativity of teacher’s teaching is the capability of teachers who keep developing materials or the subject matter and capable of creating an interesting , quiet and also can be modify the lessons.Creativity in learning, also is a very important thing and for that requiring teachers to demonstrate and showing the creative process.One of alternatives that can has made the schools is to create effective, efficient and creative learning .Research aims to know the development of teacher’s creativity in enhancing creative learning. Methods used is the method of descriptive qualitative.The subject of the study is; school participant, teachers, students.This research result indicates that, creative teachers are teachers who capable of develops the ability of pedagogical, to develop life skills, increases and constructs their values, and also professionasm. All of this can be obtained in the development of Creative learning which is capable of being created in pedagogical and professional in accordance the era of globalization. Keywords: Pegagogical ability, Creativity, Creative Teacher, Creative Learning